ZINA CRIMINAL ACTION SYSTEM (Analysis of the Criminal Procedure Book and Law Qanun for Aceh Jinayah Procedure) - Erha Saufan Hadana (SHIBGHAH: Journal of Muslim Societies, 2020)
The purpose of considering is to explain the proof of opinion in the Criminal Procedure Code and the Jinayat Procedural Qanun, the position of proof of the defendant's recognition, and the mechanism in the Jinayat Procedural Qanun. The method used is normative juridical, with secondary data as supported data. The results showed the strength of the proof of the statement in the Criminal Procedure Code and the Qanun of the Jinayat Procedural Law had several differences, including the number of elections in the Criminal Procedure Code of at least two witnesses while in the Jinayat Procedural Qanun, specifically for adultery of at least four witnesses. The position of the defendant's acceptance in proving that adultery is preferred because it must be approved to be removed from sin. The admission process is divided into two, namely outside and inside the trial, outside the trial begins at the examination process at the education level, the prosecution and in the Court of the panel of judges asking again about the recognition. While the permission was received by the defendant in the trial. The defendant requested and requested permission to be uqubat hudud.